2020
DOI: 10.1038/s41598-020-68421-4
|View full text |Cite
|
Sign up to set email alerts
|

Crystals reveal magma convection and melt transport in dyke-fed eruptions

Abstract: The processes and ranges of intensive variables that control magma transport and dyke propagation through the crust are poorly understood. Here we show that textural and compositional data of olivine crystals (Mg/Fe, Ni and P) from the tephra of the first months of Paricutin volcano monogenetic eruption (Mexico, 1943–1952) record fast growth and large temperature and oxygen fugacity gradients. We interpret that these gradients are due to convective magma transport in a propagating dyke to the Earth’s surface i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 54 publications
(79 reference statements)
1
20
1
Order By: Relevance
“…By comparing the Los Hornitos olivine zoning to other strongly-zoned olivines that are interpreted to represent magma mixing, we find important differences. The magnitudes of Fo–Ni increments associated with the growth of crystal frames (∆Fo <0.6 and ∆Ni > 200 ppm) contrast with Fo–Ni variations reported for a ring tuff of Shiveluch volcano in Kamchatka 18 , Llaima volcano 17 in the Andean Southern Volcanic Zone of Chile and Paricutín in Central America 30 . At Shiveluch, primitive compositions of olivine present increments of up to ~300 ppm of Ni accompanied by increments of Fo greater than two forsterite units (∆Fo > 2), whereas at Llaima volcano, evolved olivine crystals (~Fo 74 ) present increments of Ni on the order of ~150 ppm accompanied by increments of Fo greater than 3 Fo units (∆Fo > 3).…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…By comparing the Los Hornitos olivine zoning to other strongly-zoned olivines that are interpreted to represent magma mixing, we find important differences. The magnitudes of Fo–Ni increments associated with the growth of crystal frames (∆Fo <0.6 and ∆Ni > 200 ppm) contrast with Fo–Ni variations reported for a ring tuff of Shiveluch volcano in Kamchatka 18 , Llaima volcano 17 in the Andean Southern Volcanic Zone of Chile and Paricutín in Central America 30 . At Shiveluch, primitive compositions of olivine present increments of up to ~300 ppm of Ni accompanied by increments of Fo greater than two forsterite units (∆Fo > 2), whereas at Llaima volcano, evolved olivine crystals (~Fo 74 ) present increments of Ni on the order of ~150 ppm accompanied by increments of Fo greater than 3 Fo units (∆Fo > 3).…”
Section: Resultscontrasting
confidence: 57%
“…On the other hand, chemical variations induced by the entrainment of primitive melts of distinct composition accounted for Ni reversals > ~800 ppm for mostly invariant Fo, as the case of Irazú volcano in Costa Rica 3 . A recent study on Paricutín 30 presented oscillatory zoning in intermediate Fo olivines (~Fo 78–86 ) and attributed those changes to complex magma mixing within the conduit during ascent. Compared to olivines from Los Hornitos those from Paricutín show much larger variations in major elemental zoning (∆Fo > 2).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies highlight the importance of crystal-rich plumbing systems, as crystals contain resorbed cores that belong to earlier intrusions (decades to hundreds of years) and rims that record much shorter times (e.g., Di Stefano et al 2020, Ubide et al 2019. Crystals from monogenetic or/and dike-fed eruptions record magma transport and storage times of weeks to months (e.g., Albert et al 2020, Brenna et al 2018, Pankhurst et al 2018, Ruprecht & Plank 2013, whereas magma mixing in the lower crust has been reported to occur over several centuries before eruption (e.g., Mutch et al 2019).…”
Section: Timescales Of Magma Replenishment Mixing Differentiation and Degassingmentioning
confidence: 99%
“…A fourth hypothesis is that the most Mg-rich olivine in each of the hawaiite samples does not match the expected liquidus composition due to disequilibrium induced by rapid growth of olivine. For example, Albert et al (2020) showed that the texture of olivine phenocrysts changes in a stratigraphic sequence of erupted tephra from a monogenetic cone, corresponding to variations in rapid ascent rates via fractures to the surface. However, there is no evidence that textural disequilibrium corresponds to chemical disequilibrium, as demonstrated by the olivine-melt equilibrium experiments conducted by Pu et al (2021).…”
Section: Hypothesis 4: Disequilibrium Due To Kinetics Of Rapid Growthmentioning
confidence: 99%